Piloting a minimum data set (MDS) in english care homes: a qualitative study of professional perspectives on implementation and data use - Rachael E. Carroll; Nick Smith; Sinead ER Palmer; Jennifer Kirsty Burton; Adam Lee Gordon; Ann-Marie Towers; Stacey E. Rand; Freya Tracey; Anne Killett; Lucy Webster; Barbara Hanratty; Karen Spilsbury; et al. (BMC Geriatrics)
Abstract Background Digitalisation within English care homes offers potential to make more effective use of substantial data collected by staff during care planning and recording. A pilot minimum data set was co-designed with stakeholders based on two digital care records with additional structured measures. Our objectives were to explore (1) care home staff opinions and experiences of collecting structured measures of quality of life, cognition and function for residents and (2) how a minimum data set data might be used by staff and other professionals interested in care homes. Methods Between June and October 2023 focus groups and interviews involving care home staff and Integrated Care System participants from three regions of England were undertaken. Integrated Care System staff work externally from care homes and support commissioning of services for care homes and reviewing data. We used a semi-structured topic guide. Two waves of care home focus groups were conducted after each wave of minimum data set data capture. A single wave of focus groups/interviews were undertaken with Integrated Care System participants. Reflexive thematic analysis was used to develop themes. Results Twenty-four staff from 22 care homes and 16 staff from 15 care homes participated in five wave one and four wave two focus groups respectively. Ten Integrated Care System participants from two of three study regions participated in one focus group (seven participants) and three individual interviews. Three themes were developed: the care home context and the importance of a minimum data set for care, appropriateness and relevance of quality of life measures to resident care, and data quality and purpose. Conclusions Care home staff can collect structured measures on resident quality of life, function and cognition using digital care records to contribute to a minimum data set. The data generated can inform and enhance resident care. However, implementation is an evolving process requiring support, trust-building and confidence among those collecting and interpreting data and incorporation as part of routine care.